KESULITAN KEUANGAN, KOMITE AUDIT, DAN FAKTOR LAINNYA YANG MEMENGARUHI MANAJEMEN LABA - Saputra, Gerry; Rinjani, Rinjani (E-Jurnal Akuntansi TSM, 2024)
This study was conducted to obtain empirical evidence on whether financial difficulties, audit committees and other factors affect profit management. The variety of independent variables used in this study includes financial distress, audit committee, leverage, financial stability, financial target, firm size, board size, and dividend payment. This study used a sample of 111 data from 37 companies listed in the Consumer Cyclicals and Consumer Non-Cyclicals sectors on the Indonesia Stock Exchange from 2020 to 2022. Sample selection in this study used purposive sampling and data analysis using multiple regression. Based on data analysis shows that dividend payments have an influence on profit management practices. In addition, other independent variables, such as financial hardship, audit committee, leverage, financial stability, financial targets, company size, and board size did not show any influence on profit management practices.